THE DANUBE SUBMARINE CANYON (BLACK SEA): MORPHOLOGY AND SEDIMENTARY PROCESSES - Popescu I.; Lericolais G.; Normand A.; Le Drezen E.; Panin N.; Dinu C. (My University, 2004)
The Danube Canyon is a large shelf-indenting canyon that has developed seaward of the late Pleistocene paleo-Danube valley. Mechanisms of canyon evolution and factors that controlled it are revealed by analyzing the morphology and the sedimentary structure of the canyon, as well as the main features of the continental margin around the canyon. This is based on investigation by swath bathymetry in the canyon area combined with different types of seismic data. The canyon is a major erosional trough with a flat bottom cut by an entrenched axial thalweg. The thalweg path varies from highly meandering to fairly straight in relation to the local gradient. Segments of the canyon are characterized by specific morphology, orientation and gradient along the axial thalweg. We interpret these segments in terms of canyon maturity. The sedimentary structure of the canyon documents an older phase of erosion followed by partial infilling, and thus attests for repeated cycles of canyon development. Canyon morphology is interpreted as a result of erosive sediment flows along the entrenched axial thalweg that caused downcutting into the canyon bottom and instability of the canyon walls, and hence enlargement of the canyon and expansion by headward erosion. During the last lowstand level of the Black Sea the canyon was located in an area of high sediment supply close to the paleo-Danube River mouths. This is indicated by buried fluvial channels on the shelf and by a wave-cut terrace associated with a water level situated about - 90 m below the present level. We infer that erosive flows in the canyon resulted from hyperpycnal currents at the river mouths, probably favored by the low salinity environment that characterized the Black Sea during lowstand times. Other mechanisms could have contributed to trigger sediment failure along the canyon, such as instability related to the presence of shallow gas, or the effect of a deep fault.
Keywords: Black Sea; submarine canyon; headward erosion; buried fluvial channels; wave-cut terrace; gas; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен